A bibliometric analysis on “edu-technopreneurship” topic and chance on its development in language, literature, and literacy fields - Chafit Ulya; Ulfa Rizqi Putri; Bagus Wahyu Setyawan; Nur Samsiyah; Hespi Septiana; Toerhthangquor Shuvrangshu Joyotu (Universitas Ahmad Dahlan, 2023)
The industrial revolution 4.0 era gives a huge challenge for higher education institutions. They are demanded to be able to produce skilled, competent, and creative graduates in competing their skill in regional, national, and international scopes. Edu-technopreneurship is an important issue necessarily conducted by higher education institutions to face this challenge. This study aimed to map a topic on edu-technopreneurship in scopus and a chance of its development in language, literature, and literacy fields. By using keywords of “education”, “technology”, and “entreprenership” in the scopus page, were found 1,383 documents discussing about these topics. These data were then analyzed quantitatively to see the developmental trend happening. Besides, a bibliometric analysis was conducted using VOS viewer to see the interrelation between documents. The result shows that studies on these topics have been frequently conducted and experiencing improvement significantly by the year. They are often related to economy, technique, technology, and education. However, they do not deal with langauge, literature, and literacy. It indicates that there is a big opportunity and challenge to study the “edu-technopreneurship” in language, literature, and literacy fields in the future.